A Theory on the Discontinuity in Earnings Distributions - Li, Wei (Contemporary Accounting Research, 2014)
Please note: The publisher is not responsible for the content or functionality of any supporting information supplied by the authors. Any queries (other than missing content) should be directed to the corresponding author for the article.